Music Therapy on Pain Management Among Post-Operative Patients: A Systematic Review - Sri Utami Damayanti; Eva Herawati; Suryati Suhaemia; Natalia Suraningsih; Imansyah Abd Latif Ode; Yani Sofiani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aim: This review aimed to identify and analyze the existing literature related to music therapy on pain management among post-operative patients. Methods: This study utilizes a literature review approach, with research sources drawn from three databases: Proquest, Pubmed, and Google Scholar. Four suitable articles were found after screening the articles published between 2012 and 2022 in journals in English and Bahasa, with quasi-experimental research designs and True Experiments. "Post-operative Period" AND "Music Therapy" OR "Pain Management" OR "pain management" were the keywords used for literature searching. Result: As many as four articles were found among the 1550 articles that met the criteria. This study showed that: (i) Recital prayer, such as shalawat and dzikr treatment, can be used in place of music therapy; (ii) Music picked by the participants was shown to considerably decrease the patient’s pain following open surgery, biopsy, endoscopy, and wound dressing postoperatively. Conclusions: This study indicated that music therapy or prayer therapy considerably reduced postoperative pain in post-operative patients, particularly when the music choice was picked by the participants. This study indicated that including music therapy in standard post-operative pain management may provide an effective technique for decreasing patients' pain severity for caregivers.